Estimation of the Age and Reproductive Performance of Wild-Born and Escaped Mink (Neovison vison) Caught in the Wild in Denmark - Sussie Pagh; Cino Pertoldi; Mariann Chriel; Heidi Huus Petersen; Trine Hammer Jensen; Sussi Madsen; David Chr. Evar Kraft; Toke Munk Schou; Mette Sif Hansen (Animals, 2021)
The feral mink population in Denmark consists of two groups of animals: mink born in the wild and mink that have recently escaped from farms. The aims of this study were to: (1) estimate the reproductive performance and mortality of the Danish mink born in the wild (wild-born) and mink escaped from farms (captive-born); (2) discuss the likelihood of a self-sustaining population of wild-born mink in Denmark; and (3) model the relationship between the pulp cavity width and the age of mink. During 2018, 247 wild caught mink were sent for necropsy at the Danish National Veterinary Institute. Based on body length, 112 were determined as captive-born and 96 as wild-born. The mean litter size ± SE of wild-born females was 7.6 ± 0.9 (range: 5–11 kits) and for captive-born females 5.9 ± 0.9 (range: 1–10 kits). The relationship between age (in months) of mink and pulp cavity width was highly significant. Individuals with a pulp cavity width of >35% were younger than one year. Based on fecundity, the turnover of the mink population was estimated to be 66%, and the yearly mortality was estimated at 69%. Hence, the population is slightly declining. In conclusion, a feral reproducing mink population in Denmark persists without a continuous influx of captive-born mink from farms.